English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

x^3 - 2x^2 = 63x

2007-10-28 12:17:14 · 3 answers · asked by Anonymous in Science & Mathematics Mathematics

3 answers

x^3 - 2x^2 - 63x = 0

factor out x to get

x(x^2 - 2x - 63)=0

x(x-9)(x+7)=0

x=0, -7, 9

2007-10-28 12:20:46 · answer #1 · answered by Anonymous · 0 0

x^3 - 2x^2 = 63x
x^3 - 2x^2 - 63x = 0
x(x^2 -2x - 63)=0
x(x-9)(x+7) = 0
x = 0, 9, -7

2007-10-28 19:21:37 · answer #2 · answered by ironduke8159 7 · 0 0

step 1 factor out the x

x(x^2 -2x -63)=0
x*(x-9)*(x+7) = 0

Thus: x = {-7,0,9}

2007-10-28 19:21:01 · answer #3 · answered by mikenwu99 3 · 0 0

fedest.com, questions and answers